Increases in Absolute Temperature Stimulate Free Calcium Concentration Elevations in the Chloroplast. (4th December 2018) - Lenzoni, Gioia; Knight, Marc R
Abstract: Plants need to sense increases in temperature to be able to adapt their physiology and development to survive; however, the mechanisms of heat perception are currently relatively poorly understood. Here we demonstrate that in response to elevated temperature, the free calcium concentration of the stroma of chloroplasts increases. This response is specific to the chloroplast, as no corresponding increase in calcium is seen in the cytosol. The chloroplast calcium response is dose dependent above a threshold. The magnitude of this calcium response is dependent upon absolute temperature, not the rate of heating. This response is dynamic: repeated stimulation leads to rapid attenuation of the response, which can be overcome by sensitization at a higher temperature. More long-term acclimation to different temperatures resets the basal sensitivity of the system, such that plants acclimated to lower temperatures are more sensitive than those acclimated to higher temperatures. The heat-induced chloroplast calcium response was partially dependent upon the calcium-sensing receptor CAS which has been shown previously to regulate other chloroplast calcium signaling responses. Taken together, our data demonstrate the ability of chloroplasts to sense absolute high temperature and produce commensurately quantitative stromal calcium response, the magnitude of which is a function of both current temperature and stress history.